2005
DOI: 10.1172/jci25445
|View full text |Cite
|
Sign up to set email alerts
|

Uterine sensitization-associated gene-1 (USAG-1), a novel BMP antagonist expressed in the kidney, accelerates tubular injury

Abstract: Dialysis dependency is one of the leading causes of morbidity and mortality in the world, and once endstage renal disease develops, it cannot be reversed by currently available therapy. Although administration of large doses of bone morphogenetic protein-7 (BMP-7) has been shown to repair established renal injury and improve renal function, the pathophysiological role of endogenous BMP-7 and regulatory mechanism of its activities remain elusive. Here we show that the product of uterine sensitization-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(129 citation statements)
references
References 57 publications
8
121
0
Order By: Relevance
“…30,49,50 Primary antibodies against the following proteins were used for immunostaining: hHBegf (R&D Systems), aquaporin 1 (Abcam, Inc., Cambridge, MA), Tamm …”
Section: Histologic Studies and Immunostainingmentioning
confidence: 99%
See 1 more Smart Citation
“…30,49,50 Primary antibodies against the following proteins were used for immunostaining: hHBegf (R&D Systems), aquaporin 1 (Abcam, Inc., Cambridge, MA), Tamm …”
Section: Histologic Studies and Immunostainingmentioning
confidence: 99%
“…50 Specific primers were designed using Primer Express software (Applied Biosystems, Foster City, CA). Serially diluted cDNA was used to generate the standard curves for each primer.…”
Section: Quantification Of Mrna By Real-time Rt-pcrmentioning
confidence: 99%
“…The Sostdc1 knockout allele was generated by replacing both Sostdc1 exons with an in-frame LacZ reporter [177]. LacZ stains were performed on fixed tissues (fractured and intact femora at days 3, 7, 10, 14, and 21 post-fracture, n=3 per group, per time point, male mice) of Sostdc1 +/-and Sostdc1 -/-mice as previously described [187] with minor modifications.…”
Section: Lacz and Immunohistological Stainingmentioning
confidence: 99%
“…Sostdc1, a paralog of Sost also known by several other names including SostLike, Wise, Ectodin and Usag-1 arose by segmental gene duplication and was previously studied in the context of tooth development, kidney disease, cancer progression, hair follicle formation, and embryo implantation [103,[177][178][179][180][181]. Recently, we have shown that Sostdc1 also contributes to limb morphogenesis [104], and its expression in the periosteum suggests that it may also play a role in bone maintenance and repair.…”
Section: Introductionmentioning
confidence: 99%
“…Such extracellular BMP signaling inhibitors include noggin, 114 gremlin, 115 CRIM1, 116 DAN/cerberus, 117 vertebrate chordin 118 and uterine sensitization-associated gene-1 (USAG-1). 119 In contrast, Kielin/chordin-like protein (KCP) protein is an extracellular protein that enhances the activity of BMP7 by amplifying the physical interaction of BMP7 with its receptor. 120 BMP7 is a member of the TGF-b superfamily.…”
Section: Perspective: Anti-fibrosis Therapymentioning
confidence: 99%